Integrasi Prinsip Syariah dalam Pengelolaan Modal Kerja dan Keputusan Pembiayaan: Tinjauan Teoritis: Integration of Sharia Principles in Working Capital Management and Financing Decisions: Theoretical Review - Dessy Boegiyati; Segaf; Parmujianto (Mu'allim, 2024)
This study aims to analyzes working capital management and financing in general. Basically, working capital management is a form of managing the company's current assets and current liabilities with the aim of achieving a balance between profit and risk so that in the future it can make a positive contribution to company value, namely increasing profits and reducing risk. The condition of the company is influenced by working capital management in increasing and controlling its liquidity. Where a company must provide sufficient working capital in order to carry out the company's operations. In addition, increases or decreases in liquidity can be seen from the company's working capital. Financing management is very important for Islamic financial institutions because by implementing good financing management, Islamic financial institutions in particular will be able to maintain healthy financial performance and reduce the risk of bad financing. This research is quantitative research with a descriptive approach. To minimize the risks that occur, financing management from the perspective of Islamic financial institutions must be carried out based on the precautionary principle contained in the financing analysis which includes 5C analysis and 7A analysis.